Applied linguistics: A consumer's view. (15th March 2018) - Swan, Michael
Abstract : Like many EFL teachers of my generation, I side-stepped into the profession. While doing post-graduate research at Oxford in the early 1960s, I took a job one summer vacation teaching English in a local language school. Though I had no idea how to do this, I enjoyed the work, and kept on a few hours' teaching in the next academic year. As time went on, it became clear that I had somewhat more talent for this type of activity than for academic research, and I became a full-time teacher, subsequently opening my own school of English.